Answer:
x = 14+
Step-by-step explanation:
If 14 + 14 = 28
Then
28 > 27 is true.
It might be wrong but this is how i solved it: i used the elimination method to solve this and got x is 3-4y and y is all real numbers
first multiply the top equation by 5 and then you get:
5x+20y=15
-5x-20x=-15
since all the numbers are canceled out it is all real numbers.
then for x since you can’t substitute the y back in i just did:
x=3-4y
i just moved over the 4y
and to prove it you can say you substituted several points and they all worked
hope this helped let me know if you have any questions
The vertex form of the equation f(x) = x^2 - 3x, is f(x) = (x - 3/2)^2 - 9/5
<h3>How to rewrite the
quadratic function?</h3>
The quadratic function is given as:
f(x) = x^2 - 3x
Differentiate the function
f'(x) = 2x - 3
Set the function to 0
2x - 3 = 0
Add 3 to both sides
2x = 3
Divide by 2
x = 3/2
Set x = 3/2 in f(x) = x^2 - 3x
f(x) = 3/2^2 - 3 * 3/2
Evaluate
f(x) = -9/5
So, we have:
(x, f(x)) = (3/2, -9/5)
The above represents the vertex of the quadratic function.
This is properly written as:
(h, k) = (3/2, -9/5)
The vertex form of a quadratic function is
f(x) = a(x - h)^2 + k
So, we have:
f(x) = a(x - 3/2)^2 - 9/5
In f(x) = x^2 - 3x,
a = 1
So, we have:
f(x) = (x - 3/2)^2 - 9/5
Hence, the vertex form of the equation f(x) = x^2 - 3x, is f(x) = (x - 3/2)^2 - 9/5
Read more about vertex form at
brainly.com/question/24850937
#SPJ1
Answer: I prefer long division because that is the method I understand
Step-by-step explanation:
I prefer long division because that is the method I understand .for example
(x^2+3x+2) ➗ (x+2)
x+1
|````````````````````````
x+2 x^2+3x+2
-(x^2+2x)
````````````````````````````
x+2
- (x+2)
````````````````````````
0
`````````````````````````
therefore (x^2+3x+2) ➗ (x+2)=x+1